Platelet-derived growth factor triggers translocation of the insulin-regulatable glucose transporter (type 4) predominantly through phosphatidylinositol 3-kinase binding sites on the receptor. - Kamohara, S (1995)
Insulin is the only known hormone which rapidly stimulates glucose uptake in target tissues, mainly by translocation to the cell surface of the intracellular insulin-regulatable glucose transporter (glucose transporter type 4, GLUT4). We have developed a cell line for direct, sensitive detection of GLUT4 on the cell surface. We have suggested that insulin-activated phosphatidylinositol (PI) 3-kinase may be involved in the signaling pathway of insulin-stimulated GLUT4 translocation. We report that platelet-derived growth factor (PDGF), which stimulates PI 3-kinase activity, triggers GLUT4 translocation in Chinese hamster ovary (CHO) cells stably overexpressing the PDGF receptor and in 3T3-L1 mouse adipocytes. Using mutant PDGF receptors that cannot bind to Ras-GTPase-activating protein, phospholipase C-gamma, and PI 3-kinase, respectively, we obtained evidence that PI 3-kinase binding sites play a key role in the signaling pathway of PDGF-stimulated GLUT4 translocation in the CHO cell system.